Application of the automatic control theory for searching rational ways of technical diagnostics and improvement of technical characteristics of 2Е36 stabiliser - Kasimov, Anatoliy; Shpinda, Yevhen; Horbov, Oleksii; Kovtunov, Yurii; Kolobov, Igor; Krasnoshapka, Yuri (Національний технічний університет "Харківський політехнічний інститут", 2019)
The subject matter ofthe article is the process of troubleshooting a BMP-2 fire control system The goal of the study is the developing a fault finding algorithm in this system and to offer suggestions for improving the technical characteristics of the weapon stabilizer based on the analysis of design and circuit solut ions and technical characteristics of the BMP-2 fire control system. The tasks to be solved are: to conduct an analysis of the BMP-2 fire control system as a closed automatic control system provide suggestions for improving the performance of the stabilizer; to draw up a block diagram of a rational technical diagnostics of the 2E36 stabilizer and to propose a method for troubleshooting. General scientific and special methods of scientific knowledge are used. The following results are obtained. It is proposed to improve the technical characteristics of the 2E36 stabilizer by reducing the number of gyrotachometers from four to two with a parallel increase in the remaining signal branching, as well as improving the speed characteristics by installing an additional power source - a capacitor battery, for short-term and short-term engines. A rational technical diagnostics block scheme of the 2E36 stabilizer has been drawn up and methods of troubleshooting in the form of rigidity tuning cards, damping and vibration of the gun and turret stabilizer have been proposed. The diagnostic methods of elemental and group inspections are analyzed. Based on the analysis, the basic algorithms for the diagnostic process of tower and gun stabilization were de veloped. Thanks to this in the area of the task, personnel and repair units will be able to ensure the combat readiness of the equipment as quickly as possible. Conclusions. Gun stabilizers and turrets are closed automatic control systems based on the principle of adjusting the deviation of the adjustable value from a predet ermined value. The objects of regulation in these stabilization systems are the cannon and the tower, and the adjustable values are their angular velocities. Feedback optimization involves reducing the number of gyrotachometers from four to two, which will increase the power reserve and give more opportunities for further stabilizer upgrades. Acceleration of the accelerator of the executive motor can be accomplished by installing a capacitor battery. The most long-term step in the process of repairing the complexity of complex systems is the process of finding failed items. The scheme of rational technical diagnostics provides the basic algorithms for carrying out the diagnostic process of stabilization of the tower and the gun, which allows to search for problems with maximum efficiency.

Предметом дослідження є процес пошуку несправностей в системі управління вогнем БМП-2. Метою дослідження є на основі аналізу конструктивних і схемних рішень та технічних характеристик системи управління вогнем БМП-2 розробити алгоритм пошуку несправностей у даній системі та надати пропозиції щодо покращення технічних характеристик стабілізатора озброєння. Задачі: Провести аналіз системи управління вогнем БМП-2 як замкненої системи автоматичного регулювання; надати пропозиції щодо покращення технічних характеристик стабілізатора; скласти структурну схема раціональної технічної діагностики стабілізатора 2Е36 та запропонувати методику пошуку неполадок. Отримані такі результати. Запропоновано покращення технічних характеристик стаблізатора 2Е36 за рахунок зменьшення кількості гіротахометрів з чотирьох до двох з паралельним збільшенням розгалудження сигналів від тих, що залишилися, а також покращення швидкісних характеристик за рахунок встановлення додаткового джерела живлення – конденсаторної батареї для короткочасного збільшення потужності та скорочення часу на розгін двигунів. Складена структурна схема раціональної технічної діагностики стабілізатора 2Е36 та запропоновані методики пошуку неполадок у вигляді карток налаштування жорсткості, демпфірування і вібрації стабілізатора гармати та башти. Проаналізовані діагностичні методи поелементних і групових перевірок. На основі аназізу розроблені основні агоритми для проведення діагностичного процесу стабілізацій башти і гармати. Завдяки цьому у зоні виконання завдання особовий склад та ремонтні підрозділи зможуть максимально швидко забезпечувати боєготовність техніки. Висновки. Стабілізатори гармати і башти являють собою замкнені системи автоматичного регулювання, які ґрунтуються на принципі регулювання по відхиленню регульованої величини від заданого значення. Об'єктами регулювання в цих системах стабілізації являється гармата і башта, а регульовані величини – їх кутові швидкості. Оптимізація зворотного зв’язку передбачає скорочення кількості гіротахометрів з чотирьох до двох, що дозволить збільшити запас потужності і дасть більше можливостей для подальшої модернізації стабілізатора. Прискорення розгону виконавчого двигуна можливо здійснити за допомогою встановлення конденсаторної батареї. Найбільш довгостроковим етапом в процесі відновлення справності складних систем є процес пошуку елементів які відмовили. Схема раціональної технічної діагностики передбачає основні алгоритми для проведення діагностичного процесу стабілізації башти і гармати, що дозволяє проводити пошук неполадок з максимальною ефективністю.
Використання теорії автоматичного управління для пошуку раціональних шляхів технічної діагностики та покращення технічних характеристик стабілізатора озброєння 2Е36
Keywords: functional logic diagram; structural diagram of rational technical diagnostics of the stabilizer; methods of troubleshooting; фунціонально-логічна схема; структурна схема раціональної технічної діагностики стабілізатора; методики пошуку неполадок